2004
DOI: 10.1038/sj.npp.1300544
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Nicotine Exposure on Primate Brain Development and Attempted Amelioration with Supplemental Choline or Vitamin C: Neurotransmitter Receptors, Cell Signaling and Cell Development Biomarkers in Fetal Brain Regions of Rhesus Monkeys

Abstract: Studies in developing rodents indicate that nicotine is a neuroteratogen that disrupts brain development by stimulating nicotinic acetylcholine receptors (nAChRs) that control neural cell replication and differentiation. We administered nicotine to pregnant Rhesus monkeys from gestational day 30 through 160 by continuous infusion, achieving maternal plasma levels comparable to those in smokers (30 ng/ml). Fetal brain regions and peripheral tissues were examined for nAChR subtypes, other neurotransmitter recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 95 publications
2
78
0
Order By: Relevance
“…For example, several studies have shown lower autonomic arousal and vigilance levels in children of mothers who smoked during pregnancy (Horne, Franco, Adamson, Groswasser, & Kahn, 2004;Kristjansson et al, 1989;Raine, 2002). Measures of arousal and vigilance might be specifically sensitive to prenatal smoking, because without continued nicotinic intake after birth, the increased number of nicotinic cholinergic receptor binding sites that have been formed as a consequence of in utero-nicotine exposure may be understimulated (Oncken et al, 2003;Raine, 2002;Slotkin et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies have shown lower autonomic arousal and vigilance levels in children of mothers who smoked during pregnancy (Horne, Franco, Adamson, Groswasser, & Kahn, 2004;Kristjansson et al, 1989;Raine, 2002). Measures of arousal and vigilance might be specifically sensitive to prenatal smoking, because without continued nicotinic intake after birth, the increased number of nicotinic cholinergic receptor binding sites that have been formed as a consequence of in utero-nicotine exposure may be understimulated (Oncken et al, 2003;Raine, 2002;Slotkin et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Functional polymorphisms in these genes have been associated with aggressive antisocial behavior (Davidge et al, 2004;Volavka, Bilder, & Nolan, 2004). Exposure to nicotine and carbon monoxide has also been shown to affect catecholaminergic and serotonergic neuromodulation (Slotkin et al, 2005;Xu, Seidler, Ali, Slikker, & Slotkin, 2001). The fact that a genetic predisposition toward antisocial behavior and smoking during pregnancy seem to result in similar neurobiological changes in the central nervous system might increase the likelihood that they reinforce each other's impact (Moffitt et al, 2005).…”
Section: Limitations and Recommendations For Further Studiesmentioning
confidence: 99%
“…Testing for such interactions is important both methodologically, because sole use of covariates could mask key effects, and developmentally, because specific combinations of adverse conditions early in life might increase risk for persistent antisocial behavior beyond the simple sum of such risk factors (Raine, 2002). A combination of maternal prenatal smoking and parental antisocial behavior might be particularly harmful (see Moffitt, Caspi, & Rutter, 2005) because they are both associated with hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS) abnormalities in offspring (parental antisocial behavior: Brennan et al, 1997;Van Goozen & Fairchild, 2006;maternal prenatal smoking: Horne, Franco, Adamson, Groswasser, & Kahn, 2004;Slotkin et al, 2005). We do not know if maternal prenatal smoking and parental history of antisocial behavior interact in the prediction of offspring physical aggression, but there are some indications prenatal smoking interacts with factors associated with parental antisocial behavior.…”
mentioning
confidence: 99%
“…Since each neural cell contains a single nucleus (Winick and Noble, 1965), the DNA concentration (DNA per unit tissue weight) assesses the cell packing density, whereas the DNA content (DNA per region) gives an index of the total number of cells (Bell et al, 1987;Slotkin et al, 1984;Winick and Noble, 1965). Neuronal growth and the accompanying cell enlargement necessitate a rise in the ratio of total protein/ DNA (Qiao et al, 2003(Qiao et al, , 2004Slotkin et al, 2005) and the formation of neuritic projections elicits a corresponding rise in the contribution of membrane proteins relative to other cell proteins (membrane/total protein ratio). Accordingly, we assessed these indices as well.…”
Section: Introductionmentioning
confidence: 99%